Enhancement of Esterification of Propionic Acid with Isopropyl Alcohol by Pervaporation Reactor - Ajit P. Rathod; Kailas L. Wasewar; Chang Kyoo Yoo (Journal of Chemistry)
With increasing cost of raw materials and energy, there is an increasing inclination of chemical process industries toward new processes that result in lesser waste generation, greater efficiency, and substantial yield of the desired products. Esterification is a chemical reaction in which two reactants carboxylic acid and alcohol react to form an ester and water. This reaction is a reversible reaction and the equilibrium conversion can be altered by varying the process parameters. Pervaporation reactor can enhance the conversion by shifting the equilibrium of reversible esterification reactions. Polyvinyl alcohol-polyether sulfone composite hydrophilic membrane was used for pervaporation-assisted esterification of propionic acid with isopropyl alcohol. The experiments were carried out in the presence of sulphuric acid as a catalyst at 50°C to 80°C with various reactants ratios. The esterification was carried out for catalyst loadings of 0.089 kmol/m3 to 0.447 kmol/m3. The molar ratios of isopropyl to propionic acid used for the experiment were 1 to 1.5. Maximum conversion was obtained for the ratio of 1.4. Also effect of other parameters such as process temperature and catalyst concentration was discussed. It was found that the use of pervaporation reactor increased the conversion of the propionic acid considerably.